Femoral Vein Wall Thickness Measurement May Be a Distinctive Diagnostic Tool to Differentiate Behcet's Disease with Intestinal Involvement and Crohn's Disease - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (SPRINGER, 2021)
Backgrounds Behcet's disease (BD) and Crohn's disease (CD) cannot be easily differentiated in young adults presenting with nonspecific gastrointestinal (GI) manifestations due to similar extraintestinal manifestations. We recently showed that increased common femoral vein (CFV) thickness is a distinctive feature of BD, rarely present in other inflammatory or vascular diseases with a specificity higher than 80% for the cutoff value of >= 0.5 mm. We suggest that CFV thickness measurement with ultrasonography (US) can be a diagnostic tool for BD. Aims To assess the diagnostic performance of CFV thickness measurement in the differential diagnosis of BD and CD. Methods Patients with BD (n = 69), CD (n = 38), and healthy controls (HC) (n = 38) were included in the study. Bilateral CFV thickness was measured with Doppler US. Results Both right and left CFV thicknesses were significantly higher in BD compared to HC and CD (for right: 0.76 mm vs 0.33 mm, for left: 0.78 mm vs 0.35 mm,p < 0.001 for both). CFV thicknesses in CD were similar to HC (p > 0.05 for both). CFV thickness was also similar between BD patients with and without GI involvement (p = 0.367). The diagnostic cutoff values of >= 0.5 mm for CFV thickness performed well against to both CD and HCs for discrimination of BD. The sensitivity and specificity rates were > 85% for both HC and CD. Positive and negative predictive values in our tertiary clinical setting were > 90%. Conclusion We found significantly lower CFV thickness in CD compared to BD. Our results suggest that CFV wall thickness measurement is a distinctive diagnostic tool for the differentiation of BD and CD and can be helpful in daily practice for the differentiation of two diseases.
Keywords: Behcet's disease; Crohn's disease; Differential diagnosis; Vein wall thickness; Diagnostic; Ultrasound; INFLAMMATORY-BOWEL-DISEASE; MANIFESTATIONS; FREQUENCY; CONSENSUS; FEATURES; CRITERIA; RISK